Negotiating environmental change : new perspectives from social science - Leach, Melissa; Berkhout, F.; Scoones, Ian. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
This collection provides a comprehensive assessment of these critical interconnections and reveals how social scientists are making an invaluable contribution to the creation of more science and just livelihoods in a future world.
Includes index.
rpm 13/06/13
Loans
Keywords: Environmental policy; Environmental policy - Research; Great Britain